Management and leadership in schools: management. (Journal of Parents and Teachers, 2016)
The following article deals with the school’s leadership and management. It refers to the abilities and competences that a leader has to be. In addition, it highlights the organizational and pedagogical leadership’s importance and characteristics related to the principal’s profile, and therefore, the educational project that each school needs to have.
Keywords: education; leadership; management; pedagogy; organization; educational project; school; principal; leader.